Encouraging Local Unity and Regional Solidarity: A Cross-audience Metaphor Analysis of Dr. Mahathir’s Business Speeches (LSP International Journal, 2017)
Metaphors are one of the most common discourse tools used by orators as a communication strategy to persuade, communicate with, and convey their ideologies to their audience. This power of metaphor comes from its ability to create a clear and vivid picture of a concept or a topic in the audience’s mind making the audience perceive that concept or topic as the orator wants them to. Thus the usage of metaphors seems to be bound to the audience in the first place. Hence, drawing upon Charteris-Black’s (2004) Critical Metaphor Analysis Approach, this study analyzed 10 national and 15 international business speeches delivered by Dr. Mahathir Mohamad in the year 2000 in order to understand how ‘economic development’ as the main topic in both speech types was represented by metaphors across national and international audience. The findings revealed a significant relationship between the used metaphors and the addressed audience: metaphors of War, Unfair Game, and Miracle were used in international speeches to portray the economic gap between the developed and developing countries and to call for unity and solidarity among Southeast Asian countries; while metaphors of Plant, Cake/Pie, and Music were used in national speeches to call for Malaysians’ patience, trust in the government’s policies, and national harmony promising economic prosperity in return.